Ketogenic Diet Efficacy in the Treatment of Intractable Epileptic Spasms - Kayyali, Husam R.; Gustafson, Megan; Myers, Tara; Thompson, Lindsey; Williams, Michelle; Abdelmoity, Ahmad (Pediatric neurology, 2014)
To determine the efficacy of the ketogenic diet in controlling epileptic spasms after failing traditional antiepileptic medication therapy. This is a prospective, case-based study of all infants with epileptic spasms who were referred for treatment with the ketogenic diet at our hospital between 2009 and 2012. All subjects continued to have epileptic spasms with evidence of hypsarrhythmia or severe epileptic encephalopathy on electroencephalography despite appropriate medication treatments. The diet efficacy was assessed through clinic visits, phone communications, and electroencephalography. Quality of life improvement was charted based on the caregiver's perspective. Twenty infants (15 males) were included in the study. The mean age at seizure onset was 4.5 months. Age at ketogenic diet initiation was 0.3 to 2.9 years (mean 1.20, standard deviation 0.78). Fifteen patients had epileptic spasms of unknown etiology; three had perinatal hypoxic ischemic encephalopathy, one had lissencephaly, and one had STXBP1 mutation. Fifteen infants failed to respond to adrenocorticotropin hormone and/or vigabatrin before going on the ketogenic diet. Three months after starting the diet, >50% seizure reduction was achieved in 70% of patients (95% CI 48-86). These results were maintained at 6- and 12-month intervals. All eight of the patients followed for 24 months had >50% seizure reduction (95% CI 63-100). At least 90% seizure reduction was reported in 20% of patients at 3 months (95% CI 7-42), 22% (95% CI 8-46) at 6 months, and 35% (95% CI 17-59) at 12 months. The majority of patients (63%) achieved improvement of their spasms within 1 month after starting the diet. Sixty percent of patients had electroencephalographic improvement. All caregivers reported improvement of the quality of life at the 3-month visit (95% confidence interval 81-100). This ratio was 94% at 6 months (95% CI 72-99) and 82% at 12 months (95% CI 58-95). The ketogenic diet is a safe and potentially effective method of treatment for patients with epileptic spasms, especially those who do not respond to customary medication therapies.